Minimum term contracts in the absence of handset subsidies - David Mu\~noz; José María Rodríguez; Juana Santamaría (International Telecommunications Society (ITS), 2015)
Minimum term contracts (“MTC”) are widely used in the communications sector. They are frequently associated with equipment subsidies. But they are also offered to customers in exchange for a discount. MTCs usually come with an early termination fee (“ETF”), a penalty the customer has to pay for leaving the company before the end of the contract period. This paper provides an economic rationale for the use of MTCs when they are not linked to handset subsidies, discusses the design of the ETF in these cases, and assesses the potential implications in terms of market efficiency. We show that MTCs can be used as a screening device to segment the market between customers with differing preferences for being able to change provider at any time. This may result in a higher level of output and lower average prices.
Keywords: 330